Spatial Patterns of Travel Behavior in Rapidly Urbanizing Areas: A Case Study of Sango-Ota, Ogun State, Nigeria - S. O. Gbadebo; A. B. Muili; E. M. Dairo (Journal of Applied Sciences and Environmental Management)
Spatial interaction theory serves as a foundational framework for understanding the flow and patterns of transport movements within urban and rural areas. Hence, the objective of this paper was to evaluate the spatial patterns of travel behavior among residents in Sango-Ota, Ogun State, Nigeria, by assessing the factors influencing mobility, including socio-economic characteristics, land use distribution, and population density using primary data collected via structured questionnaires administered to 357 households across different residential zones. Data obtained show that majority of trips (54.4%) are work – related, with average trip lengths between 5.1 and 10 km. A significant statistical variation exists in daily trip frequency among different spatial structures (F = 22.082, p = 0.000). Findings indicate that urbanization has led to increased travel demands and changing mobility patterns, necessitating targeted transportation policies. The study underscores the importance of integrating urban planning with transportation strategies to improve mobility in rapidly growing urban areas.